Frequency of Non-Alcoholic Fatty Liver Disease in Obese and Non-Obese Diabetics and Its Relation to Duration of Diabetes Mellitus (Medical Forum Monthly, 2024)
Objective: To find out the frequency of non-alcoholic fatty liver disease in obese and non-obese diabetics and its relation to duration of diabetes mellitus.Study Design: Cross sectional studyPlace and Duration of Study: This study was conducted at the Department of Medicine, Sheikh Khalifa Bin Zaid Al-Nahyan hospital Rawlakot from July 2017 to December 2017.Materials and Methods: Patients with type 2 diabetes mellitus presenting to outpatient department were enrolled and their age, weight, height and duration of diabetes mellitus were noted. Body mass index (BMI) was calculated using formula BMI = (weight in kilograms) / (height in meters2). Ultrasound abdomen was used to detect the presence and absence of fatty liver disease. SPSS version 20 was used for analysis of data. Chi-square test was applied to assess the significance of difference of fatty liver disease in normal weight, over weight, class I obese, class II obese and class III obese diabetics and relation of duration of diabetes mellitus with presence or absence of fatty liver disease.Results: Out of 200 patients 10% were of normal weight, 44% were overweight and 41% had class I obesity while none had class II or class III obesity. Incidence of fatty liver was 50% in patients with normal weight, 76% of patient who were over-weight and 97% of patients with class I obesity. Also its incidence was 71% in patients with duration of disease between 1 to 4 years, 91% amongst patient with duration of diabetes between 5 to 8 years and 100% of patients with duration of diabetes between 9 to 12 years.Conclusion: In type 2 diabetic patients Frequency of non-alcoholic fatty liver disease is high in patients who are obese as compared to patients who are non-obese and its incidence increases with increase in duration of diabetes